Residual Stress Analysis in Pipe Welding ASTM A106 Grade B Using FEM Simulation - Hamdani Hamdani; Turmizi Turmizi; Bukhari Bukhari; Edi Saputra; Ilyas Yusuf (Journal of Welding Technology, 2022)
Fabrication technology has also penetrated the oil and gas industry, such as in the case of joining materials, one of the applications being made is the connection of pipes by welding. In the welding process, the heat distribution is uneven and the cooling rate is fast, resulting in residual stresses. This is indicated by changes in the microstructure in the weld area and the Heat Affecting Zone (HAZ), causing the material to become hard but brittle (brittle). This can cause structural failure in the connection area. This study investigates the residual stresses in pipe welding ASTM A 106 Grade B using the finite element method with ANSYS R17.2 software. The simulation is divided into 2 steps, namely thermal and structural analysis. The variation used in this simulation is the electric current as the welding heat input. The electric current is 110 A with an effective heat input of 2337.5 Watts with a maximum residual voltage of 399.59 MPa, 2762.5 Watts with a current of 130 A of 420.01 MPa, 3400 Watts with a current of 160 A of 454.06 MPa. The simulation shows that an increase in electric current in the range of 110 to 160 A can imply an increase in residual voltage. A welding heat input is obtained with the minimum residual voltage value, namely at a current of 110 A with an effective heat input of 2337.5 watts.